Acute effects of physiological fatigue indicators on the motor reaction speed among the karate players at different level of competition - Bilalic, J.; Bajric, O.; Lacic, O.; Huremovic, T.; Huremovic, D. (Sports Science and Health, 2018)
This study was conducted on a sample of 40 senior and junior male and female karate fighters, chronological ages 18 to 27 from the Tuzla Canton, who are part of the regular training and competition process. The aim of this paper is to determine the differences in the motor reaction speed among the karate players with the same specializations but at different levels of competition, in conditions of fatigue induced by intense physical work in combination with complex visual signalization, which determines certain karate techniques. The study was conducted with the application of sophisticated technologies used in sport that enable the collection of data. The light stimuli was generated by the usage of the RIR 102 reaction meter and the quantitative valorization of the investigated parameters was carried out by a sophisticated kinematic analysis of the videos collected using two high-speed Casio Exilim EX-F1 digital cameras synchronized with the data from the Polar Team heart monitoring system. By processing and analyzing data, it was concluded that fatigue induced by situational conditions such as performing a series of strikes that simultaneously generate muscular, cognitive and sensory strain, produces negative effects on reaction time of the karate players. The intensity of limiting factors grows gradually in function of time, but is manifested differently in relation to the international and state level of competition.